Immersive gathering: insights into virtual workplace meetings - Held, Niels; Soeter, Marieke; van Gent, Sophie; Wiezer, Noortje; Loots, Gjalt; Niamut, Omar (Frontiers in Virtual Reality, 2024)
In the aftermath of the COVID-19 pandemic, the prevalence of remote business meetings through videoconferencing platforms such as Zoom and Microsoft Teams has substantially increased. While remote meetings provide benefits such as increased efficiency, flexibility, and environmental sustainability, they may also reduce meeting engagement, hamper conversational flow, or cause fatigue. This study investigates whether social Extended Reality technology can serve as a viable alternative for videoconferencing for remote business meetings. Employees from three distinct organizations in the Netherlands convened through Meta Horizon Workrooms, a collaborative virtual platform. Afterwards, participants were inquired about their perspectives on Extended Reality during semi-structured interviews that focused on the meeting's engagement, conversational flow and the system's usability. The study's findings highlight the benefits of Extended Reality for remote business meetings, as participants reported improved interaction, more togetherness, and a better conversational flow. Embodied virtual reality was identified as useful in supporting nonverbal communication by allowing for more natural interaction and turn-taking, similar to face-to-face interactions. Nonetheless, challenges associated with avatar realism and the developing technological state of Extended Reality present barriers, rendering current widespread adoption a difficult task.